O Projeto Alfabetização Solidária e seu impacto na atuação dos professores e nas práticas de letramento de jovens e adultos de Maracanaú-CE - Medeiros, Ana Luzia Cavalcante (2009)
The objective of this research is to investigate the impact of the method of teaching in the lives of those who have been instructed and made literate through the Project Alfabetização Solidária – AlfaSol, working in conjunction with the Federal University of Ceará and the Municipality of Maracanaú, Ceará, during the year 2006. The research also tries to discover how those who finished the Project got into the work force as well as examening the formation process of those responsable for the literacy of 293 students, divided into fifteen classrooms in various localities in the municipality. The research tried to verify the initial hypothesis that the students examined had a very low level of writing ability, and indeed left the program iliterate. We started from the presupposition that literate environments stimulated individuals to become literate and permitted those with recently acquired abilities to further develop their literacy capability. A case study of a descriptive nature was carried out through a stratified sample. Our instrument for investigating was a questionaire given both to the students and those responsable for the teaching to discover the level of literacy among them.